The changing aspect of partnership business structure in Malaysia / Hamizah Abdul Rahman ... [et al.] - Abdul Rahman, Hamizah; Othman, Nurul Syahira; Tengku Zainal Mulok, Tengku Adida; Kamarul Zaman, Liziana; Wan Hashim, Wan Murshida (Universiti Teknologi MARA, Perlis, 2021)
Partnership business structures have been accepted as a major venture capital vehicle, which is generally opted for by small and medium businesses, or by professionals that are prohibited from incorporating under the respective laws. The main objectives of this paper are first to highlight the changes in the legal attributes of general partnership structures, resulting from its evolution to limited liability partnerships (LLP). Secondly, it investigates the suitability of the LLP structure for some business partners, particularly professionals, as businesses grow with rising trade costs and litigation issues that have forced partners to take precautions regarding business liabilities. These situations have led to a tendency for existing partnerships to change from general to a hybrid entity (LLP). Thirdly, it also analyses the benefits and drawbacks of LLPs as an option for general partnerships. This paper adopts doctrinal and statutory analysis as the research methods, whereby secondary analysis of relevant documents and legal acts that govern partnership businesses are referred to. Some interviews were conducted with the LLP partners, registration bodies, and bankers, to review the current implementation issues related to LLPs. This research found that the general partnership business structure has many problems, mainly related to unlimited liability and accounting procedures, which affect the obligations and protections of partners' benefits. To conclude, the question of whether LLPs is the best alternative for partners to opt for from a general partnership finds that it is the easiest choice, compared with incorporation, but many impediments occur in its implementations that must be considered by partners. although partners can protect themselves in LLPs with the partnership agreement, there are still many loopholes in its business implementation when it comes to integrity, trust, financing, reporting, sharing of profits, and other issues.